1968
DOI: 10.1111/j.1365-3059.1968.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Oviposition of Wheat Bulb Flies

Abstract: Water traps examined weekly were used to assess the activity of adult wheat bulb flies during the oviposition period in late July, August and eariy September. Traps were placed at various distances up to 1 mile (1-6 km) from known sources of infestation at Whittlesey, Cambridgeshire and at Rothamsted. Most flies were caught down wind from possible emergence sites and few were caught more than ^| mile (^0-4-0-8 km) away. The distribution of flies between traps was similar in both the first and second halves of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

1968
1968
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…In spite of the presence around the study site of a "wild" shoot fly population of unknown size, our data show a significant correlation between rainfall and decrease in adult numbers; a loss in trap efficiency due to reduced sunshine and possibly to an arrestant effect of rain (MILES 1951, BARDNER et al 1968), also occurred.…”
Section: Discussioncontrasting
confidence: 61%
“…In spite of the presence around the study site of a "wild" shoot fly population of unknown size, our data show a significant correlation between rainfall and decrease in adult numbers; a loss in trap efficiency due to reduced sunshine and possibly to an arrestant effect of rain (MILES 1951, BARDNER et al 1968), also occurred.…”
Section: Discussioncontrasting
confidence: 61%
“…Tray samples can be taken more rapidly than core samples and, because of the smaller bulk of soil, also require less time for processing in the laboratory. Bardner, Lofty, Huston & Maskell (1968) have shown that most flies do not travel more than 0-8 km to oviposit so that areas found to be at risk are unlikely to change rapidly…”
Section: Discussionmentioning
confidence: 99%
“…In both years, four traps per field were used, each one being placed in a different part of the field. This was a practical number to visit and an irnprovem.ent over the one trap per field used by Bardner et al (1968). It also allowed reasonable estimates of a total catch to be made when some traps were upset during cultural operations.…”
Section: Methodsmentioning
confidence: 99%
“…They then fly to bare soil, either fallow areas or between rows of plants, to lay eggs. Wliile studying dispersal over a limited area in East Anglia, Bardner et al (1968) placed a single white water-trap at each of 15 potential oviposition sites and recorded the numbers of flies caught during July and August. In September, egg populations at these sites were estimated from soil-cores.…”
Section: Introductionmentioning
confidence: 99%